Academic Stress among Future Nurses: A Bangladeshi Perspective on First Year BSc and Diploma Students - Chinna Chadayan; Dipa Rani Roy; Melba Sahaya Sweety (Fakultas Kesehatan, Universitas Nurul Jadid, 2026)
ABSTRACTBackground: Academic stress can hinder learning, retention, and program success in prelicensure nursing education, particularly where rapid program expansion limits faculty and student support. In Bangladesh, BSc and Diploma nursing tracks are expanding, yet comparative data on stress among first-year students remain scarce. Methods: A descriptive cross-sectional study was conducted among 120 randomly selected first-year nursing students (BSc=60, Diploma=60) at a college in Savar, Dhaka. A supervised web-based questionnaire collected socio-demographic information and Academic Stress Scale scores (0–120), categorized as low (0–24), mild (25–49), moderate (50–74), high (75–99), and extreme (100–120). Statistical analyses included chi-square, t-tests, and ANOVA (α=.05). Results: Stress levels were low (12.5%), mild (30.8%), moderate (39.2%), and high (17.5%), with no extreme stress reported. Mean stress was higher in BSc students (59.73±21.01) compared to Diploma students (45.80±22.25) (p=.001). Stress was significantly associated with age (p = .004), course (p = .010), and family type (nuclear > joint; p = .048). Conclusion and Recommendations: Mild-to-moderate stress predominated, with higher burdens among BSc students and those from nuclear families. Early stress screening, structured mentoring, and counselling referral pathways are recommended to reduce attrition and enhance performance. Multi-site longitudinal studies are needed to validate and extend these findings.